O estado da arte: previdência social e complementar brasileira na perspectiva do envelhecimento - Pinto, Cláudia Campestrini (2017)
The twenty-first century demographic revolution signals the rapid aging process in the world, revealing a historical milestone in contemporary society that is the Longevity Revolution, making existing notions of old age and retirement rethought, with increased life expectancy. An elderly population presents social and economic challenges, with systematic and endogenous changes in economic behavior, specially on savings. This scenario requires adjustments and reforms in social security and stimulus in pension funds helping people to a more balanced financial situation throughout the life, generating welfare of the families. The objective of this research was to outline the scientific approaches to aging in Brazil, identifying in these approaches the intention of collaborating with the definitions of public policies in the scope of social security and pension funds. The method used was the bibliographic review called "state of the art" of the retrospective and secondary type. With the definition of the descriptors the research was carried out in theses and dissertations published during the last 10 years (2006 to 2016). In the qualitative analysis, it was observed that the need for reforms and adjustments in social security and the importance of fostering complementary social security as a long-term savings instrument provides social welfare for families and contributes, above all, to the country's development. It is concluded that aging engenders great human development and challenges in the elaboration of public policies in diverse areas, mainly creates opportunities in new products and services. Facing challenges in a provident way will allow the aging of people with dignity and security in a comprehensive social transformation of contemporary society